2012
DOI: 10.1039/c2ob25345c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of masked oxo-sulfinamides in asymmetric synthesis

Abstract: This short perspective reports on the synthesis and applications of a class of chiral amino carbonyl compounds, masked oxo-sulfinamides where the amine is protected with an N-sulfinyl moiety and the carbonyl group is protected as the ketal or 1,3-dithiane. These polyfunctionalized chiral building blocks are prepared by addition of organometallic reagents to masked oxo-sulfinimines (N-sulfinyl imines) or the addition of oxo-organometallic reagents and lithio-1,3-dithianes to sulfinimines. Because unmasking of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
1
11
0
1
Order By: Relevance
“…立体化学是有机化学教学中的一个重要概念,与之相关的手性、不对称合成等在生命科学、药 物、材料等学科中均有着极其重要的应用。由于涉及的概念抽象,特别是不对称合成涉及的对映选 择性、非对映选择性等多种概念,传统的理论教学虽能在一定程度上帮助学生理解立体化学中的诸 多概念,但对于初学者来说,这些概念可能比较抽象,难以产生直观的体会。学生经常会见到同时 出现对映异构体和非对映异构体的反应,但往往很难明确指出两者的异同。为了解决这一问题,不 妨利用教学实验让学生对立体化学产生直观而明确的印象。在建设"双一流"高校和"双一流"学 科的过程当中,实验的设计更应符合学生的知识水平,更应适合本科阶段人才培养的要求,更应为 学生之后的科研学习铺平道路。因此,本科教学迫切地需要一个合适的实验,帮助本科生理解非对 映异构体,产物 dr 值等概念。 由于教学实验受限于有限的时间、有限的规模和条件,以及对实验内容安全性、可操作性等的 要求,开发此类实验还是有一些挑战和困难。目前,在不对称合成领域,科学家已经报道了非常多 的优秀的不对称合成的方法,但是不可否认的是,很多不对称合成反应或耗时较长,或所需温度苛 刻,或选择性过高或过低导致缺乏具有演示性的教学意义。因此,需要一个简单高效的实验,同时 清晰地阐述对映异构体和非对映异构体。通过手性助剂参与的不对称合成,通过底物诱导产生非对 映选择性,清除辅基后便可得到对映体富集的产物,这类反应除了具有较高的非对映选择性,与其 相关的研究往往比较透彻,对其反应机理的了解也比较深入 [1] 。在众多手性助剂中 [2][3][4][5][6] ,Evans 助剂 已被两所学校的本科有机化学实验室用于示范实验 [7,8] 。这些实验不仅覆盖了有机化学中的许多重要 方向,同时强调了手性助剂在引入非对映选择性时的作用。尽管如此,现有的化学教育文献中,仍 然缺少对不对称合成的深入探索,如反应机理、立体化学概念等方面。显而易见,本科实验教学仍 然需要一个包含了这些基本概念(非对映异构体、dr 值等)以及相应表征方法的演示实验。基于 Davis [9][10][11] 和 Ellman [12][13][14] 等在亚磺酰亚胺合成与应用上的进展,人们对锌参与的 N-叔丁基亚磺酰亚 胺的烯丙基化反应开发了多种反应条件的实验 [15][16][17][18][19] ,我们在 2015 年成功开发了一个基于溶剂调控 的不对称合成的教学实验 [19b]…”
Section: 引言unclassified
“…立体化学是有机化学教学中的一个重要概念,与之相关的手性、不对称合成等在生命科学、药 物、材料等学科中均有着极其重要的应用。由于涉及的概念抽象,特别是不对称合成涉及的对映选 择性、非对映选择性等多种概念,传统的理论教学虽能在一定程度上帮助学生理解立体化学中的诸 多概念,但对于初学者来说,这些概念可能比较抽象,难以产生直观的体会。学生经常会见到同时 出现对映异构体和非对映异构体的反应,但往往很难明确指出两者的异同。为了解决这一问题,不 妨利用教学实验让学生对立体化学产生直观而明确的印象。在建设"双一流"高校和"双一流"学 科的过程当中,实验的设计更应符合学生的知识水平,更应适合本科阶段人才培养的要求,更应为 学生之后的科研学习铺平道路。因此,本科教学迫切地需要一个合适的实验,帮助本科生理解非对 映异构体,产物 dr 值等概念。 由于教学实验受限于有限的时间、有限的规模和条件,以及对实验内容安全性、可操作性等的 要求,开发此类实验还是有一些挑战和困难。目前,在不对称合成领域,科学家已经报道了非常多 的优秀的不对称合成的方法,但是不可否认的是,很多不对称合成反应或耗时较长,或所需温度苛 刻,或选择性过高或过低导致缺乏具有演示性的教学意义。因此,需要一个简单高效的实验,同时 清晰地阐述对映异构体和非对映异构体。通过手性助剂参与的不对称合成,通过底物诱导产生非对 映选择性,清除辅基后便可得到对映体富集的产物,这类反应除了具有较高的非对映选择性,与其 相关的研究往往比较透彻,对其反应机理的了解也比较深入 [1] 。在众多手性助剂中 [2][3][4][5][6] ,Evans 助剂 已被两所学校的本科有机化学实验室用于示范实验 [7,8] 。这些实验不仅覆盖了有机化学中的许多重要 方向,同时强调了手性助剂在引入非对映选择性时的作用。尽管如此,现有的化学教育文献中,仍 然缺少对不对称合成的深入探索,如反应机理、立体化学概念等方面。显而易见,本科实验教学仍 然需要一个包含了这些基本概念(非对映异构体、dr 值等)以及相应表征方法的演示实验。基于 Davis [9][10][11] 和 Ellman [12][13][14] 等在亚磺酰亚胺合成与应用上的进展,人们对锌参与的 N-叔丁基亚磺酰亚 胺的烯丙基化反应开发了多种反应条件的实验 [15][16][17][18][19] ,我们在 2015 年成功开发了一个基于溶剂调控 的不对称合成的教学实验 [19b]…”
Section: 引言unclassified
“…The stereoselective construction of C-N bonds is a highly desirable reaction. [96][97][98][99][100][101][102] Conjugate amination of Michael systems is the general approach to access β-amino carbonyl compounds 71. [103][104][105][106] The reaction makes use of the inherently high nucleophilicity of the nitrogen atom, which in turn causes side reactions and hampers enantioselective addition.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…[103][104][105][106] The reaction makes use of the inherently high nucleophilicity of the nitrogen atom, which in turn causes side reactions and hampers enantioselective addition. [96][97][98][99][100][101][102] Zhou et al used protoncoupled electron transfer (PCET) to convert N-H groups into nitrogen-centered radicals under mild conditions (Scheme 28). 107 The electron-deficient nature of such radicals, which makes direct addition to α,β-unsaturated compounds unfavorable, was bypassed by applying Δ-RhO as the Lewis acid catalyst in combination with an additional photocatalyst.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…Readily available enantiopure sulfinylimines also constitute valuable molecules in asymmetric synthesis [46]. Indeed, Petneházy et al [47] reported the synthesis of optically enriched α-amino-Cphosphinic acids using ethyl phenylphosphinate and chiral N-sulfinylaldimines.…”
Section: Stereoselective C-p Bond Formation (Addition Of Phosphorus Cmentioning
confidence: 99%
“…For example, following the principle of activation of imines through hydrogen bonding, Tan et al [49] carried out the hydrophosphinylation reaction of the N-tosyl imines 18a-g with arylphosphinates and alkylphosphinates in the presence of catalytic amounts of the guanidinium salt 19·HBArF4 in a CH2Cl2:toluene mixture and K2CO3 as a base at −40 °C, obtaining the α-amino-C-phosphinates 20a-k in 71%-93% yield and 3:1-16:1 diastereoisomeric ratio, with preference for the diastereoisomers (RC,SP)-20a-k with 82%-94% enantiomeric excess (Scheme 13). Readily available enantiopure sulfinylimines also constitute valuable molecules in asymmetric synthesis [46]. Indeed, Petneházy et al [47] reported the synthesis of optically enriched α-amino-Cphosphinic acids using ethyl phenylphosphinate and chiral N-sulfinylaldimines.…”
Section: Chiral Catalystmentioning
confidence: 99%